Integrasi STEM-Problem Based Learning melalui Daring Terhadap Keterampilan Berpikir Kritis Mahasiswa Pendidikan Biologi - Nurul Fadhilah*; Nurdiyanti Nurdiyanti; Anisa Anisa; Muhammad Wajdi (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
The development of technology and information in the 21st century supports the implementation of online learning during the pandemic. The learning process that uses the right approach and learning model will be more effective when combined with the use of technology. The purpose of this study was to determine the effect of STEM-PBL integration through online learning on the critical thinking skills of biology education students. The research was conducted on students of the Biology Education Program in Unismuh Makassar with Pretest Posttest Control Group Design. The researchdata were collected using a test of critical thinking skills in ten valid essay questions.Hypothesis testing using independent sample t-test. The results showed that there was significant result of STEM-PBL integration on students' critical thinking skills. The improvement of critical thinking skills can be seen from the N-gain value of two classes, where the experimental class got N-gain value of 0.65 and the control class was 0.39. The average N-gain value for both classes was in the medium category. Furthermore, hypothesis testing using the average value of N-gain and obtained a significant value 0.05. Based on the results, it can be concluded that learning process that integrates STEM-PBL has a positive influence on students' critical thinking skills